Bangladesh Public Libraries' Response to COVID-19 Pandemic / Begum, D., Roknuzzaman, M., & Shobhanee, M. E. (2022). Public libraries’ responses to a global pandemic: Bangladesh perspectives. IFLA Journal, 48(1), 174–188. https://doi.org/10.1177/03400352211041138 - Dettman, David (Evidence Based Library and Information Practice, 2023)
Objective – Examine quantitative and qualitative data to determine the level of preparedness and capacity to provide key resources during the recent COVID-19 global pandemic with the goal of recommending measures to better cope with future similar situations.Design – Online questionnaire and semi-structured interviews. Descriptive statistics were used to analyze quantitative data, followed by a narrative analysis of the qualitative data.Setting – Public libraries in Bangladesh.Subjects – Heads of the libraries such as directors, librarians, or librarians-in-charge.Methods – A survey was distributed to all 71 government public libraries in Bangladesh administered and governed by the Department of Public Libraries under the Ministry of Cultural Affairs. The survey elicited 50 valid responses, resulting in a response rate of 70%. A structured form questionnaire was prepared using Google Forms and included 12 closed-ended questions with multiple options and one open-ended question to collect librarian views on handling services and key functions post pandemic. Telephone interviews were conducted with eight librarians from the district public libraries.Main Results – The data revealed that all the libraries reported having some level of preparedness for pandemics and disasters. However, few libraries reported high levels of confidence in this regard. For example, 82% responded that they either had a “low” or a “minimum” preparedness for dealing with a pandemic. The survey revealed that none of the responding libraries were fully open to provide user services during the COVID-19 pandemic while 100% were open for administrative functions. Additionally, 72% reported having some sections open but others closed, while 22% indicated that the library only provided specified services, most of these in an online environment. Only 12% indicated that they provided access to mobile library services.The libraries responses to crisis management included creating public awareness through social media campaigns (50%), supporting other government bodies to mitigate the pandemic (46%), providing counseling services for particular users (40%), promoting authoritative and authentic national and global strategies on the pandemic for the public (34%), providing pandemic-related information via phone or email on demand (32%), and distributing relief to affected people (30%). Other activities included organizing online social and cultural programs to reduce public anxiety with special reference to vulnerable groups (24%), online staff training (22%), monitoring and supervising government programs (20%), and providing research data on the pandemic (10%).The response to needs regarding redesigning library programs and services for the post-pandemic world revealed that 90% of libraries identified a need for a dedicated online service platform, 80% saw the need to create policies related to health and safety, while 72% indicated a need for more emphasis on digital content. The responses indicated 56% were in favor of introducing innovative online services.Conclusion – In response to the results of their study, the authors make several recommendations regarding helping the libraries of Bangladesh to cope with consequences of future pandemics similar in scale to COVID-19. The first recommendation is to move away from “providing services in a traditional manner,” while developing dedicated online platforms running on high-bandwidth Internet connections (Begum et al., 2022, p. 183). These include introducing a secure cloud-based library automation system to provide a robust and stable information gateway. The development of digital resources should also be a priority. This includes both the digitization of library resources and more widespread access to an increasing number of subscription databases.The data indicated a strong desire among librarians to introduce innovative library services which the authors identify as digitized content delivery, remote access to online resources, online chat reference, current awareness services, online programming mirroring face-to-face programming, home delivery service for books, strategic disaster policy development, online information literacy programs, online career counseling, and leadership along with online training, workshops, and seminars. The authors conclude that:libraries face challenges, such as transitioning to virtual services, breaking long-established service models, funding for digital resources and its impacts on library operations in the future, enforcing social distancing measures, creating social awareness, and the lack of formal pandemic plans and policies …. (Begum et al., 2022, p. 179)